2001
DOI: 10.1258/0022215011908315
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinthine involvement in Behçet's syndrome

Abstract: We report the neuro-otological ndings in 26 consecutive patients with de nite and probable Behçet's syndrome unselected for audiovestibular complaints. Auditory and/or vestibular abnormalities were found in 19 (73 per cent) patients, with auditory involvement in 14 (54 per cent) and vestibular in 10 (38.5 per cent) of patients. Peripheral involvement was more common than central involvement for both auditory and vestibular lesions. Bilateral cochlear hearing impairment was the most common audiological nding, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 30 publications
1
37
1
1
Order By: Relevance
“…On the other hand, the involvement of the cochlea was more frequent than the involvement of the vestibular system. The lack of correlation between the dysfunction of the cochlea and the vestibular system can be explained by their different vascular supply [Pollack et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the involvement of the cochlea was more frequent than the involvement of the vestibular system. The lack of correlation between the dysfunction of the cochlea and the vestibular system can be explained by their different vascular supply [Pollack et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…The rates of SNHL reported in the literature are 29.5-55% in rheumatoid arthritis [Kastanioudakis et al, 1995;Salvinelli et al, 2004], 24-55% in Behçet's disease [Ak et al, 2004;Evereklioğlu et al, 2001;Pollack et al, 2001], 46% in the Sjögren syndrome [Tumiati et al, 1997] and 58% in systemic lupus erythematosus [Andonopoulos et al, 1995]. SNHL in rheumatic diseases is bilateral, especially at high frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be due to vasculitis, ossicular involvement, neuritis or ototoxicity of the drugs used for the treatment of rheumatologic diseases (18). Thus, hearing loss may be seen in conductive, sensorineural or in mixed pattern in secondary AIED (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(19)(20). Özcan et al suggested middle ear involvement for the reason of hearing loss in RA (18).…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte, otoakustik emisyon (OAE) gibi diğer testleri de içeren ve daha büyük örneklem büyüklüğüne sahip başka çalışmalara da ihtiyaç vardır. (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The inner ear pathologies caused by these disorders are commonly mild and slowly progressive whereas primary AIED is characterized by sudden onset, commonly bilateral, fluctuant and progressive sensorineural hearing loss (SNHL) with accompanying vertigo in some occasions.…”
Section: öZetunclassified